Serosurveys to detect SARS-CoV-2 antibodies among high-risk groups in six urban cities of Odisha, India - Kanungo, Srikanta; Giri, Sidhartha; Bhattacharya, Debdutta; Kshatri, Jaya Singh; Palo, Subrata Kumar; Parai, Debaprasad; Turuk, Jyotirmayee; Praharaj, Ira; Mansingh, Asit; Dash, Girish Chandra; Choudhary, Hari Ram; Pattnaik, Matrujyoti; et al. (The Journal of Infection in Developing Countries, 2023)
Introduction: Personnel involved in essential services or residing in high-risk areas during the COVID-19 pandemic are at increased risk of getting infected. We evaluated the proportion of personnel infected in several high-risk groups in Odisha using seroprevalence studies. Methodology: During July to November, 2020, individuals from multiple high-risk groups in 6 urban cities (Bhubaneswar, Berhampur, Cuttack, Malkangiri, Paralakhemundi, and Rourkela) in Odisha, India, were recruited to the study after obtaining written informed consent. Blood samples collected from the study participants were tested for IgG antibodies against COVID-19 in Roche Cobas e441 (Roche Diagnostics, Rotkreuz, Switzerland). Information on socio-demographic variables, association with a confirmed or suspected case, and other details were collected using an electronic data capture tool and analysed with a statistical software. Results: The overall COVID-19 seroprevalence was 34.9% (95%CI 33.6-36.2) among the 5434 individuals. The seroprevalence varied from 21.8% (95% CI, 19.6-24.1) in Rourkela to 54.9% (95% CI, 51.5-58.2) in Bhubaneswar. Seropositivity was maximum among prisoners (47.7%), followed by municipality/ sanitation staff (43.5%), and other office going staff (40.8%). Multivariate logistic regression indicated that participants aged 18-29 years, 30-44 years, residents of slums and vending zone, municipality staff, prisoners, residents of urban cities Malkangiri, Cuttack, Paralakhemundi, Bhubaneswar and those with previous history of COVID-19 were independent co-relates of seropositivity. Conclusions: The risk of COVID-19 varied among the high-risk groups of Odisha. Periodic seroprevalence studies in future are essential to protect the high-risk personnel involved in frontline activities during the pandemic.